Cartesian product of two symmetric starter vectors of orthogonal double covers - R.A. El-Shanawany; M. Higazy; H. Shabana; A. El-Mesady (AKCE International Journal of Graphs and Combinatorics, 2015)
An orthogonal double cover (ODC) of a graph H is a collection G={Gv:v∈V(H)} of |V(H)| subgraphs of H such that every edge of H is contained in exactly two members of G and for any two members Gu and Gv in G, |E(Gu)∩E(Gv)| is 1 if u and v are adjacent in H and it is 0 if u and v are nonadjacent in H. In this paper, we are concerned with the Cartesian product of symmetric starter vectors of orthogonal double covers of the complete bipartite graphs and using this method to construct ODCs for new graph classes.